Coronary cytoskeletal modulation of coronary blood flow in the presence and absence of type 2 diabetes: the role of cofilin - McCallinhart, Patricia E.; Stone, Kathlyene R.; Lucchesi, Pamela A.; Trask, Aaron J. (Frontiers in Physiology, 2025)
BackgroundCoronary resistance microvessels (CRMs) from type 2 diabetic (T2DM) mice and pigs are less stiff compared to normal, a finding that is dictated by less stiff coronary vascular smooth muscle cells (VSMCs). Cofilin is an endogenous actin regulatory protein that depolymerizes filamentous (F)-actin, and portions of F-actin bound to cofilin are less stiff compared to their unbound F-actin counterparts. In this study, we hypothesized that altering the actin cytoskeleton modifies VSMC stiffness, which contributes to changes in coronary blood flow in normal and T2DM conditions.Methods and resultsUtilizing phalloidin staining, we found that F-actin was significantly reduced in T2DM CRM VSMCs, and we showed cofilin expression was increased in T2DM by proteomics and Western blot analysis. Cofilin knockdown in both human and mouse coronary VSMCs using siRNA significantly increased F/G actin ratio. Cofilin knockdown also caused a significant increase in elastic modulus by atomic force microscopy of coronary VSMCs. Treatment with Latrunculin B, an actin disruptor, significantly decreased VSMC elastic modulus. Acute Latrunculin B infusion into the coronary circulation of ex vivo isolated Langendorff mouse hearts increased peak coronary blood flow.ConclusionTogether, we demonstrated that the CRM VSMC actin cytoskeleton is altered in T2DM to favor less stiff cells, and pharmacological manipulation of the actin cytoskeleton alters VSMC biomechanics. This study is also the first to demonstrate that coronary cellular modulation of mechanics can acutely modulate coronary blood flow.